Real-time Face Recognition System Using Deep Learning Method - Wirdiani, Ayu; Darma Putra, I Ketut Gede; Sudarma, Made; Hartati, Rukmi Sari; Lofiana, Lennia Savitri Azzahra (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 14 No 1 (2023): Vol. 14, No. 1 April 2023, 2023)
Face recognition is one of the most popular methods currently used for biometric systems. The selection of a suitable method greatly affects the reliability of the biometrics system. This research will use Deep learning to improve the reliability of the biometric system and will compare it with the SVM method. The Deep Learning method will be adopted using the Siamese Network with the YoloV5 detection method as a real-time face detector. There are two stages in this research: the registration process and the recognition process. The registration process is image acquisition using YoloV5. The image result will be saved in the storage folder, and the preprocessing and training process will use the Siamese Network. The face feature model will be stored in the database. The recognition process is the same as the registration, but the feature extraction result will be embedded and compared with the already trained models . The accuracy rate using the Siamese model was 94%.